Prostatic needle biopsies following primary high intensity focused ultrasound (HIFU) therapy for prostatic adenocarcinoma: histopathological features in tumour and non-tumour tissue. Issue 8 (1st June 2012) - Ryan, Paul; Finelli, Antonio; Lawrentschuk, Nathan; Fleshner, Neil; Sweet, Joan; Cheung, Carol; van der Kwast, Theodorus; Evans, Andrew
Abstract : Aims: High intensity focused ultrasound (HIFU) is currently offered as primary treatment for patients with clinically localised prostate cancer. Data on histopathological features of post-treatment biopsies are limited. Methods: Pretreatment biopsies were identified in 45 men (age range 41–85) who received primary HIFU therapy. Post-HIFU biopsies were performed in 30 of these patients (67%) at mean 14.1 months (95% CI 11.7 to 16.5) follow-up, 22 due to rising PSA and eight as part of routine follow-up. Biopsies were examined for presence, distribution and extent of adenocarcinoma, Gleason scores, use of standard immunohistochemistry and ablative tissue changes were attributable to HIFU. Results: In post-HIFU biopsies performed for biochemical failure, 17/22 (77%) contained adenocarcinoma; 4/22 (18%) had higher post-HIFU Gleason score; 3/22 (14%) had newly recognised bilateral involvement; and 4/22 (18%) had higher percentage tissue involvement compared with pre-HIFU biopsies. Of cases without rising post-HIFU PSA, 2/8 (25%) routine follow-up biopsies contained adenocarcinoma. Stromal fibrosis was the commonest finding in non-tumour post-HIFU biopsy tissue (17/30, 57%) with coagulative necrosis occurring in fewer cases (4/30, 13%) and over a shorter follow-up interval than cases showing fibrosis (8.5 (0.2–16.8) vs 15.3 (11.5–19.1) months). Treatment effects in tumour cells precluding the assignment of Gleason scores or use of immunohistochemistry in post-HIFU biopsies were not identified. Conclusion: Post-HIFU biopsies are positive in more than 75% of patients with elevated or rising PSA. Stromal fibrosis is common but the tissue effects of this modality do not appear to impair pathologists' ability to detect and grade adenocarcinoma in follow-up biopsies.